Non-invasive Hemodynamic Monitoring of Fluid Resuscitation in Cirrhotic Patients with Acute Kidney Injury - El Hadidy, Samir; Albadry, Ahmed; Radwan, Waheed; Metwaly, Amna; Farouk, Khaled (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Fluid management of patients with liver cirrhosis and acute kidney injury (AKI) is a complex problem requiring accurate assessment of the intravascular volume status and the cause of the AKI. Echocardiography used in various hemodynamic monitoring as a quick, easy, bedside, and non-invasive tool with great sensitivity. AIM: This study aims to evaluate echocardiography as a non-invasive hemodynamic monitoring tool for the assessment of volume status and cardiac function before and after volume expansion in patients with liver cirrhosis presented by AKI. PATIENTS AND METHODS: This study included 120 patients with liver cirrhosis and AKI. All patients were subjected to clinical evaluation, laboratory assessment of kidney and liver functions, and echocardiographic assessment of inferior vena cava (IVC) collapsibility index, left ventricular outflow tract velocity time integral (LVOT VTI) variability index, and cardiac output (CO). RESULTS: Comparison between responders and non-responders to volume resuscitation regarding the echocardiographic data showed that responders had significantly higher IVC collapsibility index, LVOT VTI variability index, and % of CO increase. IVC collapsibility index and LVOT VTI variability index showed good predictive value of fluid responsiveness. CONCLUSIONS: The use of echocardiography is a good tool for hemodynamic monitoring of fluid resuscitation in cirrhotic patients with AKI. The use of echocardiography has limited the use of central venous line only to patients with hemodynamic instability requiring vasoactive support.